1994
DOI: 10.1080/03079459408418995
|View full text |Cite
|
Sign up to set email alerts
|

Natural infections byCryptosporidiumsp. in farm‐raised ducks and geese

Abstract: SUMMARYModified Ziehl-Neelsen staining and an indirect immunofluorescent assay appeared to be equally useful for monitoring natural infections with Cryptosporidium sp. in farm-raised Pekin ducklings and Danish goslings. In 73 of 128 ducklings, and in 44 of 74 goslings, Cryptosporidium sp. were detected. Tissues from the bursa of Fabricáis are most frequently positive in both species. The presence or absence of the parasite could not be correlated with clinical signs or lesions and/or poor performance of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In contrast, in the past 10 years there have been only about six reports (Trampel et al, 2000;Kimura et al, 2004;Huber et al, 2007;Soltane et al, 2007;Shemshadi et al, 2010;Smith et al, 2010). Likewise, there are only a few reports (about seven) concerning Cryptosporidium infections in ducks (Mason, 1986;Richter et al, 1994;O'Donoghue, 1995;Morgan et al, 2001;Kuhn et al, 2002;Huber et al, 2007;Amer et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, in the past 10 years there have been only about six reports (Trampel et al, 2000;Kimura et al, 2004;Huber et al, 2007;Soltane et al, 2007;Shemshadi et al, 2010;Smith et al, 2010). Likewise, there are only a few reports (about seven) concerning Cryptosporidium infections in ducks (Mason, 1986;Richter et al, 1994;O'Donoghue, 1995;Morgan et al, 2001;Kuhn et al, 2002;Huber et al, 2007;Amer et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…In the USA, an investigation indicated that 49% of ducks were carriers of Cryptosporidium (Kuhn et al, 2002). A study conducted in Germany showed a 57% (73/128) prevalence rate in ducks (Richter et al, 1994), whereas in Australia only one of 97 ducks examined was positive (Mason, 1986). In a more recent study, 3.4% (5/148) of Ruddy Shelduck (Tadorna ferruginea) examined in China were Cryptosporidium-positive (Amer et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Although both methods are commonly applied to detect C. parvum antigens (JEX et al, 2008), they may be useful for the diagnosis of avian cryptosporidiosis (RICHTER et al, 1994;GRACZYK et al, 1996;ROHELA et al, 2005;PAGÈS-MANTÉ et al, 2007).…”
Section: Diagnosis Of Cryptosporidiosis Among Birdsmentioning
confidence: 99%
“…In addition, the host range for Cryptosporidium galli was extended. Cryptosporidium muris and Cryptosporidium andersoni were also identified in a tawny frogmouth and a quail-crested wood partridge, respectively.Cryptosporidiosis is one of the most prevalent parasitic infections in domesticated, caged, and wild birds (33), and the parasite has been reported in more than 30 avian species worldwide, belonging to orders Anseriformes, Charadriiformes, Columbiformes, Galliformes, Passeriformes, Psittaciformes, and Struthiniformes (5,6,9,10,13,14,15,16,17,20,22,23,28,31,32,35,38,39). However, few studies have examined the genetic diversity of Cryptosporidium sp.…”
mentioning
confidence: 99%